2018
DOI: 10.1136/rmdopen-2017-000598
|View full text |Cite
|
Sign up to set email alerts
|

Definitions and reliability assessment of elementary ultrasound lesions in giant cell arteritis: a study from the OMERACT Large Vessel Vasculitis Ultrasound Working Group

Abstract: ObjectivesTo define the elementary ultrasound (US) lesions in giant cell arteritis (GCA) and to evaluate the reliability of the assessment of US lesions according to these definitions in a web-based reliability exercise.MethodsPotential definitions of normal and abnormal US findings of temporal and extracranial large arteries were retrieved by a systematic literature review. As a subsequent step, a structured Delphi exercise was conducted involving an expert panel of the Outcome Measures in Rheumatology (OMERA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
147
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 188 publications
(156 citation statements)
references
References 54 publications
2
147
0
7
Order By: Relevance
“…Recently, it has been defined by an Outcome Measures in Rheumatology  (OMERACT) working group as a ‘homogenous, hypoechoic wall thickening that is well delineated towards the luminal side that is visible both in longitudinal and transverse planes, most commonly concentric in transverse scans’ 26. The ‘halo’ sign at temporal arteries revealed a pooled sensitivity of 77% and a pooled specificity of 96% as compared with the clinical diagnosis of GCA 12.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been defined by an Outcome Measures in Rheumatology  (OMERACT) working group as a ‘homogenous, hypoechoic wall thickening that is well delineated towards the luminal side that is visible both in longitudinal and transverse planes, most commonly concentric in transverse scans’ 26. The ‘halo’ sign at temporal arteries revealed a pooled sensitivity of 77% and a pooled specificity of 96% as compared with the clinical diagnosis of GCA 12.…”
Section: Resultsmentioning
confidence: 99%
“…The standardization of the definitions and reliability testing by the Outcome Measures in Rheumatology (OMERACT) Ultrasound Working Group on large vessel vasculitis was per formed in order to expand the use of ultrasound in GCA and alleviate skepticism around the method . In a recent study by Chrysidis et al, in which international expert consensus was obtained using specific OMERACT methodology, the authors concluded that to a high degree ultrasound images and videos of inflamed temporal and axillary arteries can reliably document the characteristics (halo and compression signs) and diagnostic abnormalities in patients in whom GCA is suspected .…”
Section: Introductionmentioning
confidence: 99%
“…Background: Giant cell arteritis (GCA) is the most common systemic vasculitis in the elderly. The halo sign has been shown as an accepted valid test in the diagnosis of GCA in trained units [1][2] . However, to further improve the specificity, the sonographer should know some pathologies that can mimic halo signs since they also produce a hypoechoic increase of the arterial wall thickness.…”
mentioning
confidence: 99%
“…Background: Color duplex ultrasonography (CDU) is recommended as first line of imaging in patients suspected for cranial GCA [1]. However, extra-cranial involvement without temporal artery involvement is found in up to 40% of GCA patients [2].…”
mentioning
confidence: 99%